(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Parallel microchannels have been widely used in cooling of compact electronic equipment due to large contact area with liquid and availability of large mass of fluid to carry away heat. However, understanding of flow distribution for microchannel parallel system is still unclear and there still lack of studies give a clear pictures to understand the complex flow features which cause the flow maldistribution. Generally, the geometrical structure of the manifold and micro channels play an important role in flow distribution between micro channels, which might affects the heat and mass transfer efficiency, even the performance of micro exchangers. A practical design of exchanger basically involves the selection of an optimized solution, keeping an optimal balance between gain in heat transfer and pressure drop penalty. A parallel microchannels configurations consisting inlet and outlet rectangular manifold were simulated to study flow distribution among the channels were investigated numerically by using Ansys Fluent 14.5. The numerical results was validated using existing experimental data and showed a similar trend with values 1% higher than experimental data. The influence of inlet/outlet manifold area and inlet/outlet arrangement on flow distribution in channels were carried out in this study. Based on the predicted flow non-uniformity value, ðœ™, Z- type flow arrangement exhibits higher value of ðœ™, which is 8%, followed by U-type, 2.6% and the I-type, 2.49%. Thus, a better uniformity of velocity and temperature distributions can be achieved in I-shape flow arrangement. The behavior of the flow distributions inside channels is due to the vortices that occurred at manifold. Besides comparing the pressure drop for case 1(D1) and case 2(D2), it is worth to mention that, as the area of inlet and outlet manifold decrease by 50%, the pressure drop is increasing about 5%. However, the inlet/outlet area of manifold on velocity and fluid temperature distributions was insignificant.